2021
DOI: 10.1186/s12951-021-01028-7
|View full text |Cite
|
Sign up to set email alerts
|

The basic characteristics of extracellular vesicles and their potential application in bone sarcomas

Abstract: Bone sarcomas are rare cancers accompanied by metastatic disease, mainly including osteosarcoma, Ewing sarcoma and chondrosarcoma. Extracellular vesicles (EVs) are membrane vesicles released by cells in the extracellular matrix, which carry important signal molecules, can stably and widely present in various body fluids, such as plasma, saliva and scalp fluid, spinal cord, breast milk, and urine liquid. EVs can transport almost all types of biologically active molecules (DNA, mRNA, microRNA (miRNA), proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Moreover, a growing number of studies have revealed the presence of ectoproteases in EVs derived from TME. EVs are small cell-derived membrane vesicles, produced either through the endosomal pathway, giving rise to exosomes, or after budding of plasma membrane, resulting in microvesicles [243][244][245][246]. EVs obtained from the serum of cancer patients holds promise as diagnostic and prognostic parameters [229,247,248].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a growing number of studies have revealed the presence of ectoproteases in EVs derived from TME. EVs are small cell-derived membrane vesicles, produced either through the endosomal pathway, giving rise to exosomes, or after budding of plasma membrane, resulting in microvesicles [243][244][245][246]. EVs obtained from the serum of cancer patients holds promise as diagnostic and prognostic parameters [229,247,248].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
“…EVs influence tumour growth, metastasis, epithelial-to-mesenchymal transition, and drug resistance [229,[247][248][249]. Exosomes transfer various molecules from tumour cells to immune cells and neovascular cells, contributing to the escape from immune surveillance and increased angiogenesis, respectively [231,245,246]. DPP4, APN, ADAM17, and MMP2/9 were recently described in EVs derived from solid and haematological tumours [242,[250][251][252][253][254][255][256][257].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
“…Additionally, another study revealed the activation of lung fibroblasts to a cancer-associated phenotype by OS cell-derived EVs [38]. This process was shown to be dependent on TGF-β1 expression by OS EVs, highlighting how tumor cells can modulate the lung PMN to support the metastatic process [38,39]. Furthermore, OS cells not only control the formation of a favorable distant PMN but also interact with other nonneoplastic cells, supporting the creation of a pro-metastatic TME in the bone.…”
Section: How Can the Tumor Microenvironment Influence Metastasis?mentioning
confidence: 97%
“…Extracellular vesicles (EVs) are phospholipid membrane surrounded vesicles released by a variety of cells. The EVs play crucial roles in the cell-to-cell communication by transferring protein, mRNA, microRNA and other bioactive molecules in pathophysiological conditions 14 - 16 . EVs regulate cardiovascular function and structure, and are closely associated with the pathogenesis of cardiovascular diseases 17 - 19 .…”
Section: Introductionmentioning
confidence: 99%